A thorny path to a scientific realization. To 90th anniversary from the date of birth of Pr. U.I. Chirkov - V.G. Loshakov (Овощи России)
On 25th of November, 2009 is a 90th date of birthday of Juriy Ivanovich Chirkov, doctor in geography, and associate professor at meteorology and climate department of Timiriyazev Academy of Agriculture. It is him a distinguished researcher who was an inventor of theory for yield forecasting in agriculture and an author of the methods applying for accurate climate assessment used for plant adaptation to the climatic condition in different regions.